Analisis Penerapan Akuntansi Pertanggungjawaban Dengan Anggaran Sebagai Alat Pengendalian Biaya Pada Pintar Asia Swalayan Maumere - Rosa Maria Bawang; Henrikus Herdi; Yoseph Darius Purnama Rangga (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to determine the extent to which responsibility accounting is implemented at Pintar Asia Swalayan and to evaluate the efficiency of cost control at Pintar Asia Swalayan Maumere. The analytical method used in this study is descriptive method, with data analysis techniques in the form of an overview of the application of responsibility accounting which refers to the 5 conditions for implementing responsibility accounting according to Mulyadi's theory. The results obtained in this study indicate that Pintar Asia Swalayan Maumere has not fully implemented the requirements for implementing responsibility accounting because the cost budgeting process has not involved all units in the company and there is no separation of costs between controlled and uncontrollable costs. Cost control is also not fully efficient because there is still a difference between budgeted costs and actual costs.